Bioecology and Control of Yellow Mite (Polyphagotarsonemus latus (Banks)) on Sesame (Sesamum indicum L.) - . TUKIMIN (Perspektif, 2012)
Sesame crop (Sesamum indicum L.) of Pedaliaceae family originated from the African continent and was first cultivated in Ethiopia. It is cultivated for industrial raw materials, including food industry, and cooking oil. Cultivation of sesame crop has long been known in Indonesia and the species of S. indicum is widely cultivated. At the end of 2000, sesame crop received great attention because of its usefulness for health. The area planted with sesame is about 3,341 ha with a production of 1,475 thousand tons and average productivity of 464 kg/ha. The low productivity is caused by lack of good seeds used, in, not intensive farming and pest attacks. The main pest on sesame crop is yellow mite, Polyphagotarsonemus latus that attacks young leaves. The intensity of damage caused by P. latus mites can reach 75%. This paper aims to inform the control of P. latus, one of the major limiting factors in sesame cultivation.  Life cycle of P. latus on sesame crop is very short ranging from 14 to 25 days. At  can be controlled using natural  pesticide and  polysulfide base pesticide.Keywords: bioecology, control, Polyphagotarsonemus latus (Banks),vegetable pesticides,Sesamum indicum.